Prevalence of positivity in rapid test for syphilis in campaign in Northeastern Brazil - Karinna Alves Amorim de Sousa; Telma Maria Evangelista de Araujo; Layze Braz de Oliveira; Luciana Sena Sousa (DST, 2018)
Syphilis is a systemic infectious disease caused by the Treponema pallidum bacterium of sexual transmission predominance. The cases diagnosed in Brazil increase each year, and the prevalence of syphilis during pregnancy is approximately 1%, but the reported number is lower than the expected, indicating difficulties in the diagnosis. Campaigns for the detection of syphilis are one of the strategies to enable early diagnosis and timely treatment. Objective: To survey the prevalence of rapid test reagent for syphilis and infection risk factors. Methods: Epidemiological, descriptive, transversal research. Collection was made in 2016’s Carnival in the Piauí State capital, Teresina. Population was composed of individuals who agreed to voluntarily participate through express consent (n=532), 57% women and 43% men. The testing was carried out by trained professionals, initiated by the pre-test counseling through individual interview and guarantee of confidentiality of the information. Then, the rapid test was performed by blood puncture from the digital pulp. Finally, the result was passed through post-test counseling, guidance on prevention and referral of positive cases for further investigation of the infection. Results: The prevalence of rapid test reagents for syphilis was 5.4%. A predominance of males (65.5%), browns (45%), age group 29–39 years (38%), and singles (65.5%) was observed, 8 to 11 years of school education (34.4%), 52% were tested for the first time. Regarding sexual practice, 76% reported having one to five sexual partners in the last year, and only 24.1% reported using condoms with casual partners, and 55.2% affirmed no use of condoms with fixed partners. The use of alcohol and/or other drugs prior to intercourse was reported by 86.2%. Conclusion: The prevalence found justifies the need to intensify actions that increase access to diagnosis and timely treatment for the infection control. The study shows the importance of educational campaigns and cases detection due to the good adherence of the participants, and points out that strategies should be adopted to make the population aware of the increase in cases and the ways to prevent the disease.